Enhancing the Anti-Erosive Properties of Fluoride and Stannous with the Polymer Carbopol - Ávila, Daniele Mara Da Silva [UNESP]; Augusto, Marina Gullo [UNESP]; Zanatta, Rayssa Ferreira [UNESP]; Scaramucci, Tais; Aoki, Idalina Vieira; Torres, Carlos Rocha Gomes [UNESP]; Borges, Alessandra Bühler [UNESP] (Karger Publishers, 2020)
This in vitro study investigated whether Carbopol 980 polymer could potentiate the anti-erosive effect of solutions containing sodium fluoride (F) and sodium fluoride associated with stannous chloride (FS). The dissolution of hydroxyapatite treated with the experimental solutions (F [500 ppm F-], F + Carbopol [0.1%], FS [500 ppm F- + 800 ppm Sn2+], FS + Carbopol) was evaluated. Deionized water was the negative control, and a commercial mouth rinse (AmF/NaF/SnCl2; 500 ppm F + 800 ppm Sn2+; Elmex® Erosion Protection) was the positive control. The solutions were also evaluated in an erosion-rehardening protocol, with two treatments per day, using bovine enamel specimens (n = 15) and human saliva. The acid challenge was performed using 0.3% citric acid (pH 2.6) for 2 min. Microhardness was measured at different times: baseline, after the first erosive challenge, after treatment, and after the second erosive challenge. Based on microhardness values, the demineralization, rehardening, and protective potentials were calculated. The alkali-soluble fluoride on enamel surfaces was also measured. Data were analyzed using ANOVA and Tukey tests (α = 0.05). Groups treated with FS + Carbopol showed the lowest hydroxyapatite dissolution and the highest rehardening and protective potentials. The measurement of alkali-soluble fluoride on enamel surfaces was also higher in the FS + Carbopol group. Carbopol was able to significantly increase the protective effect of the fluoridated solutions in addition to optimizing the adsorption of fluoride on the enamel surface.
Keywords: Dental erosion; Fluoride; Microhardness; Polymers